Pengaruh Content Marketing Terhadap Keputusan Pembelian Melalui Customer Engagement pada Mickey Dimsum Tebing Tinggi - Zery Febriano; Rizki wahyudi; Willy Cahyadi; Limega Candrasa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the Influence of Content Marketing on Purchasing Decisions Through Customer Engagement at Mickey Dimsum Tebing Tinggi. The research method used is a quantitative method using Smart PLS version 3.0. The questionnaire was distributed to 100 respondents. The data analysis method used in the study is the measurement model (outer model), namely the validity test, reliability test, then the structural model (inner model) including: coefficient of determination/r-square (r2) and hypothesis testing with t-statistics and indirect effect tests. The results of Smart PLS 3.0 in this study are that Content Marketing has an effect on Customer Engagement at Mickey Dimsum Tebing Tinggi, Content Marketing has an effect on Purchasing Decisions at Mickey Dimsum Tebing Tinggi, Customer Engagement has no effect on Purchasing Decisions at Mickey Dimsum Tebing Tinggi, Content Marketing has no effect on Purchasing Decisions mediated by Customer Engagement at Mickey Dimsum Tebing Tinggi.